Scientific Study of Soma and Its Use in Rituals of Somayagna: A Review - B R Divya AND H R Nagendra (IJSS Case Reports & Reviews, 2016)
A performance of sacrifi cial rituals is harmonious to all living beings of the cosmos. Th ere is a negative impact on man, society and atmosphere due to the ecological imbalance; global warming is creating a more heat and pressure on the earth. Somayaga is performed for rain formation and to balance the six seasons. Th e ingredient and rituals of the yaga appear to be a promising, scientifi c, cost-eff ective, eco-friendly method to counter the ever-increasing deadly pollution of the environment, and purify and enrich the environment. A review of various sections of Vedic literature was performed with regard to Somayaga. Th e scientifi c interpretation and researches on the sacrifi cial rituals can build a more faith and deeper understanding of such customs. Th e rituals of yaga have been observed in infl uencing the collective consciousness fi elds of the people participating in the yaga as measured by REG. Hence, for the survival of the Vedic culture, welfare of the creation and mankind Somayaga must be performed. Th e present paper is aimed to briefl y compile and bring out the studies, information, and researches on Soma as a plant, drink and its use in the rituals of Somayaga